The Effectiveness of the Use of The Result Determining-Lamp Media In Class IV Students at SDN Senden Peterongan - Sabbahul Putri Wulandari; Eny Suryowati (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2023)
Concepts in mathematics include abstract concepts, especially for elementary students. So that teachers are required to always innovate in learning so that learning is effective, not boring and students more easily understand concepts correctly. This learning requires media that is appropriate to the material and cognitive development of students. The media used in this research is result determining lamp to determine the least common multiple (LCM) and the greatest common divisor (GCF) of a number. This study aims to discuss the effectiveness of result determining-lamp media to determine the results of LCM and GCF in grade IV students at SDN Peterongan Jombang. Effectiveness in research is seen from how the average learning outcomes and whether there are significant differences in student learning outcomes with and without the result determining-lamp media. Sampling uses a saturated sample, so that all class IV is used as a sample. Based on the results of the study, it was concluded that the use of result determining-lamp media is an effective determinant of learning outcomes because the average learning outcomes of the experimental class are higher than those of the control class and through the t-test there are differences in the learning outcomes of class IV students with and without the result determining-lamp media.